Emílio: Texto e Contexto - Paiva, Wilson Alves de (Revista Portuguesa de Pedagogia, 2011)
This article aims to discuss the formation of man in the text and in the context of the book Emile, or on Education, of Jean-Jacques Rousseau. The uniqueness of its content and what is postulated in this work significantly expanded our understanding of the ideas that guided the formation of the modern man until today. What makes Rousseau a ‘landmark’ in the history of education field. His educational treatise produces a new vision of man and therefore a rich theoretical material to think the society of XXI century. Emile appears to be bold and passionate attempt to restore the natural man to live virtuously social reality. In every sense, the young Emilie is fully prepared to live his personal life, as a man, or a public life, as a dedicated citizen of any community whatsoever.